Pre-fabricated Thigh Flaps for Total Thoracic Esophageal Defects after Failed Jejunum Grafting in Esophageal Cancer Surgery - Yasushi Mochizuki; Kazuki Ueda; Masayuki Okochi; Akiyoshi Kajikawa (Journal of Plastic and Reconstructive Surgery)
Three cases of total thoracic esophageal re-reconstruction after failed jejunum grafting for esophageal cancer are described. A prefabricated long skin tube formed by a combination of tensor fascia lata and anterolateral thigh flaps was transferred to the ruined anterior chest with vascular anastomosis, with the oral intake achieved in all three patients. The prefabrication reinforced the vascularity of the long conduit by the delay effect. The prefabrication included skin grafting on the resultant raw surface; hence, another free flap to seal the longitudinal suture line of the conduit was avoided. Furthermore, the viability of the conduit was easily monitored with the previously grafted skin. However, if a high-positioned jejunostomy is unavailable, an additional free skin tube might be necessary. Postoperative leakage is quite frequent due to these patients' poor general and local conditions. Therefore, sparing large local flaps or pedicled musculocutaneous flaps around both the oral and anal anastomoses for repairing the fistula is important.